Parkin paves the path to antitumor immunity: Expanding Parkin’s role as a tumor suppressor - Kim, Hyungsoo; Ronai, Ze’ev A. (The Journal of clinical investigation, 2024)
Parkin, a ring-between-ring-type E3 ubiquitin ligase, first shown to play a critical role in autosomal recessive juvenile Parkinsonism, has recently emerged as a key player in cancer biology. Parkin is now known to serve as a tumor suppressor, and its deregulation frequently promotes tumorigenesis. In this issue of the JCI, Perego et al. expand that role by showing that Parkin expression stimulated an interferon (IFN) response to modulate CD8+ T cell activity. These findings suggest that, in addition to directly inhibiting tumor progression, Parkin enhances antitumor immune responses, highlighting it as a promising therapeutic target for cancer treatment.